Effect of dietary inclusion of Rumanol ML vegetable fat on fattening hybrid turkey broilers - M. Lalev; N. Mincheva; P. Hristakieva; M. Oblakova (Trakia Journal of Sciences)
The effect of substitution of dietary sunflower oil with vegetable fat Rümanol ML in compound feeds of turkey broilers on production and slaughter traits was investigated. To this end, two groups with 75 male broiler turkeys, one day-old, with equal body weight were formed (control and experimental) and reared throughout 16 weeks. Six-phase feeding was applied-starter І (0-3 week), starter ІІ (4-6 week), starter ІІІ (7-8 week), grower І (9-10 week), grower ІІ (11-12 week) and finisher (13-16 week). During those periods, the control group was fed rations with sunflower oil content of 3 %, 4 %, 5 %, 7 % and 8 %, respectively, whereas the experimental group-rations with feed fat Rümanol ML at the same amount as sunflower oil. The results from the experiment demonstrated that Rümanol ML used as alternative of dietary sunflower oil in turkey broilers feeds had a positive effect on the live weight during the finisher period and the weight gain throughout the entire rearing period manifested by statistically significant increase by 7.13 % and 7.17 % (p<0.001) respectively and improved feed conversion by 2.5 %. Slaughter analysis showed higher absolute values of the grill weight by 9.8 % and of breast by 10.28 % and no effect on slaughter yield and the share of valuable cuts (breast, legs, wings). The integral evaluation of replacing sunflower oil in compounds feeds for turkey poults with feed fat Rümanol ML on the basis of EPEF showed better performance by 16.64 %.